Pemanfaatan Biogas dari Limbah Ternak Sapi Sebagai Solusi Energi Terbarukan dan Peningkatan Kesejahteraan Masyarakat Desa Kuripan Kecamatan Karangawen Demak - Buchori, Achmad; Prasetyowati, Dina; Widodo, Suwarno; Kusmantoro, Adhi; Bakti, Siti Maisyaroh (Journal of Dedicators Community, 2025)
Kuripan Village in Karangawen, Demak, has significant potential for renewable energy development through the utilization of cattle waste. Unmanaged cattle waste has the potential to pollute the environment, while household energy needs remain dependent on fossil fuels. This community service activity aims to empower the community through the use of biogas from cattle waste as a renewable energy solution. Implementation methods include outreach, technical training in biogas installation construction, and assistance in operation and maintenance. The results of the activity indicate that the community is able to independently build and manage the biogas installation. The resulting biogas is used for daily cooking needs, while the waste is used as organic fertilizer. This activity not only contributes to reducing waste and greenhouse gas emissions, but also reduces household energy costs by IDR 60,000 – 90,000 per month and improves the welfare of livestock farmers.. The implications of the activity indicate that the integration of appropriate technology with active community participation can encourage the creation of sustainable, energy-independent villages